Right Atrial Thrombus Mimicking Myxoma with Subclinical Pulmonary Embolism - Artemiou, Panagiotis; Lukacin, S; Bily, B (Cardiovascular Journal, 2013)
Cardiovascular Journal Volume 6, No. 1, 2013, Page 71-73 DOI: http://dx.doi.org/10.3329/cardio.v6i1.16120